Penerapan Eco-Art Therapy dalam Pengambilan Keputusan Karir Siswa MAN 2 Kab Bandung - Dewi, Rusiani; Miharja, Sugandi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2015)
Career decision-making is one of the major challenges faced by students as they stand on the threshold of transitioning from school education to the workforce or higher education. At MAN 2 Bandung, like in many other schools, eleventh-grade students are confronted with various complex educational and career choices that require deep thinking and a mature understanding of their interests, talents, and aspirations. To address this issue, this research aims to evaluate the implementation of Eco-Art Therapy in assisting MAN 2 Bandung students with their career decision-making. The results of the research indicate that prior to participating in eco-art therapy career counseling, eleventh-grade students at MAN 2 Kabupaten Bandung experienced difficulties in making career decisions due to economic factors and a lack of career information. The process of eco-art therapy career counseling is carried out through structured stages that include initiation, transition, main stages, and conclusion. The outcome is an improvement in students' ability to make career decisions and a better understanding of themselves.